Initial Assessment of Colombian-Canadian Migration (2010)
The results presented in this paper are aim at examining and comparing the migratory events occurred betwixt two countries which have different social and economic conditions. The information developed along this text is, therefore, an initial assessment on migration between Canada and Colombia. The author used hermeneutics as a main methodological tool for conducting this study.This paper concludes that, although there are a range of motivations behind the decision to leaving one’s home country, the pursuit for better economic conditions is the dominant factor.